Internal knowledge broker and diversification: the case of Korean management research institutions. (2015) - Jang, Seung Hoon; Kim, Taewan; Choi, Donghyun
This study focusses on the organisational structure supporting the learning based on diversification strategy. The literature review exhibits that an internal knowledge brokerage institution is significantly accountable for managing knowledge in the diversified firms. The case studies of seven major Korean Chaebols, or business groups, exhibit that the managerial research institutions as internal knowledge brokers enable Korean business groups (Conglomerates) to manage knowledge from the broad areas efficiently. Both scholars and practitioners gain implications on how diversified firms can use the abundant pool of knowledge across diverse areas to support their major businesses.